Positive electrode material and preparation method thereof, positive plate and battery

Through the combination technology of nickel, cobalt, manganese, aluminum quaternary cathode material and lithium iron phosphate cathode material, the use of doping elements and optimized particle size distribution, the shortcomings in energy density, cost and safety of lithium-ion battery cathode material are solved, and the energy density, cost and safety of lithium-ion battery cathode material is achieved. Comprehensive optimization of high energy density, low cost and fast charging performance.

CN119324217APending Publication Date: 2025-01-17EVE POWER CO LTD

Patent Information

Application Number
CN202411499381.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode materials have shortcomings in terms of energy density, cost, fast charging performance and safety, especially the low energy density of lithium iron phosphate materials and the stability of ternary materials.

Method used

Using the composite technology of nickel, cobalt, manganese, aluminum quaternary cathode material and lithium iron phosphate cathode material, the lattice structure and particle size distribution of the material are improved by doping elements, the diffusion kinetics and conductive properties of Li ions are improved, and the diffusion kinetics and electrical conductivity of Li ions are improved, and the specific Mass ratio and preparation method improve the compaction density and cycle life of the material.

Benefits of technology

The cathode material with high energy density, low cost, good fast charging performance and high safety performance has been achieved, which has significantly improved the overall performance of the battery, especially under large-scale and fast charging conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005102645480000201
    Figure BDA0005102645480000201
  • Figure BDA0005102645480000211
    Figure BDA0005102645480000211
Patent Text Reader

Abstract

The invention provides a positive electrode material and a preparation method thereof, a positive plate and a battery. The positive electrode material comprises a nickel-cobalt-manganese-aluminum quaternary positive electrode material and a lithium iron phosphate positive electrode material, the chemical formula of the nickel-cobalt-manganese-aluminum quaternary positive electrode material is Li (1 + u) NivMnwCoxAlyAzO2, u is greater than or equal to 0, and v + w + x + y + z = 1; the chemical formula of the lithium iron phosphate positive electrode material is Li1 + kFe (PO4) 1 + mBn, wherein k, m and n are greater than or equal to 0; wherein A and B are both doping elements; the mass ratio of the nickel-cobalt-manganese-aluminum quaternary positive electrode material to the lithium iron phosphate positive electrode material is (0.5-5.0): (5.0-9.5). The positive electrode material has the advantages of high energy density, high safety performance and good fast charging performance. And meanwhile, a pole piece prepared from the positive electrode material can achieve high compaction density, the battery capacity is effectively improved, and the positive electrode material is relatively low in cost and is a positive electrode material with excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a positive electrode material and a preparation method thereof, a positive electrode sheet, and a battery. Background Art

[0002] Lithium-ion batteries (LiBs) have been widely used in consumer electronics, electric vehicles, aerospace and other fields due to their high energy density, high coulomb efficiency, long service life, no memory effect, low self-discharge characteristics and chemical formulas with different electrode designs. Lithium-ion batteries are composed of a complex material system, including positive electrode materials, negative electrode materials, separators, electrolytes, etc. Among them, the positive electrode material is the decisive factor in the chemical properties of lithium-ion batteries, which directly determines the energy density and safety of the battery, and thus affects the overall performance of the battery. At the same time, the proportion of positive electrode materials in the cost of lithium battery materials is as high as 30-40%, and its cost also directly determines the overall cost of the battery. Therefore, positive electrode materials play a vital role in lithium batteries and directly lead the development of the lithium battery industry. Lithium batteries are divided according to the positive electrode material system, mainly divided into lithium cobalt oxide (LCO), lithium manganese oxide (LMO), lithium iron phosphate (LFP), ternary materials (nickel cobalt manganese oxide (NCM) and nickel cobalt aluminum oxide (NCA)) and other technical routes.

[0003] At present, the mainstream cathode materials used in the lithium battery industry are lithium iron phosphate (LFP) and ternary materials (lithium nickel cobalt manganese oxide (NCM) and lithium nickel cobalt aluminum oxide (NCA)). Both materials have their own advantages and disadvantages, as follows:

[0004] (1) Regarding lithium iron phosphate (LFP) materials: Its crystal structure is olivine-type and stable. During the charge and discharge process, the insertion and removal of Li+ will basically not cause changes in the material structure. Therefore, it has good safety performance and long cycle life (at least more than 2000 times). At the same time, the production resources of lithium iron phosphate materials are abundant, and its cost is lower than other positive electrode materials. However, since the LFP particles themselves are basically insulating and have poor electronic conductivity, their rate, low temperature and fast charging performance are poor. At the same time, due to the influence of its structure, on the one hand, the powder compaction is low, and the limit theoretical calculation can only reach 2.80g / cm 3 , the actual level can only reach 2.62g / cm 3 The compaction of ternary material powder can reach 3.00g / cm 3The above differences are obvious, which indirectly affects the capacity of the single cell; on the other hand, the storage performance of the olivine structure for Li+ also leads to the relatively low energy density of the LFP material (140-160Wh / kg, up to 180Wh / kg), while the maximum energy density of the ternary material has reached 300Wh / kg, which is more than 60% higher than LFP. The energy density of the LFP material is difficult to meet the requirements of the current new energy vehicle market for long-range driving.

[0005] (2) Regarding ternary materials: their structure is layered. Currently, the most typical ternary positive electrode materials include 442, 532, 622 and 811 (Ni: Mn: Co), which have the advantages of high energy density (up to 300Wh / kg) and good fast charging performance. However, the elements Ni, Co and other elements used are precious metals, which leads to high costs. Ternary materials are layered oxides. Oxygen will be lost during the cycle process, which will promote the structural phase change and form a spinel structure. Further structural defects such as dislocations, grain boundaries and microcracks will be generated in the bulk structure. The generation of these defects will expose more new surfaces. Lithium ions pass through this interface, and active lithium ions react with the electrolyte to consume electrolyte and active lithium ions, increasing the internal resistance of the battery. The electrolyte reaction produces gas, which leads to an increase in the internal pressure of the battery, thereby affecting the stability and safety of the battery, resulting in poor stability and safety of ternary materials.

[0006] In view of this, there is an urgent need to develop a positive electrode material with high energy density, low cost, good fast charging performance and high safety performance. Summary of the invention

[0007] In order to solve the problems and deficiencies in the prior art, the present invention provides a positive electrode material and a preparation method thereof, a positive electrode sheet, and a battery. The positive electrode material has both high energy density and high safety performance, and good fast charging performance. At the same time, the electrode sheet prepared with the positive electrode material can achieve a high compaction density, effectively improving the battery capacity, and the positive electrode material has a low cost, and is a positive electrode material with excellent comprehensive performance.

[0008] According to a first aspect of the present invention, a positive electrode material is provided, including a nickel-cobalt-manganese-aluminum quaternary positive electrode material and a lithium iron phosphate positive electrode material; the chemical formula of the nickel-cobalt-manganese-aluminum quaternary positive electrode material is Li (1+u) Ni v Mn w Co x Al y A z O2, where u≥0, v+w+x+y+z=1; the chemical formula of lithium iron phosphate positive electrode material is Li 1+k Fe(PO4) 1+m B n, where k, m, n ≥ 0; where A and B are both doping elements; the mass ratio of nickel-cobalt-manganese-aluminum quaternary positive electrode material and lithium iron phosphate positive electrode material is (0.5~7.0):(3.0~9.5).

[0009] As described in the background technology, lithium iron phosphate cathode material (LFP) has good structural stability, high safety performance, and long cycle life, but its electronic conductivity is poor, resulting in poor rate, low temperature and fast charging performance, and low powder compaction density, resulting in low battery capacity and low energy density. Therefore, how to improve LFP materials to improve their electrochemical properties such as energy density, compaction density, and capacity is of great significance to whether LFP can be widely used in lithium-ion batteries.

[0010] Nickel-cobalt-manganese-aluminum quaternary positive electrode material (NCMA) is made by adding Al to the traditional high-nickel NCM positive electrode material, and has excellent properties such as high energy density and capacity. Through the doping of Al, NCMA can make up for the lack of stability of NCM and increase the proportion of nickel content, thereby greatly improving the battery capacity. And because the addition of Al elements will cause a slight loss of capacity, the addition of this element significantly improves the cycle life and thermal stability of the material. Therefore, due to the improvement of its comprehensive performance, NCMA has become a competitive choice of positive electrode material and has been widely studied and applied in recent years. However, since NCMA is also a layered oxide, even if it has a high energy density, its structural degradation under long cycles, capacity decay at high rates, and structural phase changes under high pressure will become factors that affect material safety and limit the electrochemical performance.

[0011] The present invention uses NCMA and LFP (lithium iron phosphate) both containing metal doping elements in a specific ratio to effectively make up for the deficiencies of the two positive electrode materials themselves, so that the final positive electrode material has both high energy density and high safety performance, and has excellent fast charging performance, effectively improving the compaction density of the pole piece and the battery capacity. In addition, due to the introduction of LFP, the amount of precious metal cobalt can be effectively reduced, reducing the cost of raw materials.

[0012] Specifically, firstly, a certain amount of doping elements are introduced into NCMA and LFP respectively, which can produce favorable lattice defects or widen the diffusion channel of Li ions, improve the diffusion kinetics of Li ions in the lattice, improve the ionic conductivity or electronic conductivity of the material, and thus improve the electrochemical performance of the material. Secondly, NCMA and LFP are used in a specific ratio. Because NCMA has a higher energy density and capacity, and LFP has a better cycle life and safety performance, at a specific ratio, the positive electrode material obtained by compounding these two materials can give full play to the electrochemical performance advantages of each of them, and effectively make up for the shortcomings of the two materials themselves, so that the final positive electrode material has high energy density, high safety performance, high compaction density, high battery capacity, good fast charging performance, etc., and has excellent comprehensive performance. In addition, due to the difference in the particle structure of NCMA and LFP, the compound use of these two materials can complement each other in the filling process (filling the gaps between particles), so it can effectively improve the compaction density of the material powder, effectively improve the compaction density of pure LFP, and then effectively improve the battery capacity.

[0013] Preferably, the mass ratio of nickel-cobalt-manganese-aluminum quaternary positive electrode material to lithium iron phosphate positive electrode material is (1-4): (6-9).

[0014] Preferably, the mass ratio of nickel-cobalt-manganese-aluminum quaternary positive electrode material to lithium iron phosphate positive electrode material is 2.5:7.5.

[0015] Preferably, the particle size of the positive electrode material is 0.1-2 μm, and the particle size distribution is: 0.1-0.3 μm accounts for 35-45% by mass, 0.3-0.5 μm accounts for 15-25% by mass, 0.5-1 μm accounts for 15-25% by mass, 1-1.5 μm accounts for 5-15% by mass, and 1.5-2 μm accounts for 5-15% by mass. Firstly, the overall particle size of the positive electrode material is controlled within a smaller range by the present invention, which is beneficial to increase the specific surface area of ​​the positive electrode material particles, improve the electrolyte infiltration ability, shorten the lithium ion diffusion particle size, and is beneficial to Li +The embedding and de-embedding of the positive electrode material can improve the rate performance and initial capacity of the lithium-ion battery. Secondly, the present invention further defines the specific particle size distribution. Within the above-mentioned particle size distribution range, the void volume between the particles can be further reduced, and the powder compaction density and the pole piece compaction density can be further increased, thereby improving the electrochemical performance such as the battery capacity. Due to the above-mentioned specific particle grading, especially the control of the mass proportion of 0.1 to 0.3 μm, the void volume between the particles is effectively reduced, so that the positive electrode material particles can support each other, so that the structural stability during the charging and discharging process can be effectively improved, so that the positive electrode material can be charged and discharged at a higher rate, and the fast charging performance of the positive electrode material can be effectively improved. Moreover, because the void volume between the positive electrode material particles is small, the energy density of the positive electrode material is also effectively improved.

[0016] Preferably, the doping element A includes at least one of Ti, K, Ca, Sc, V, Rb, Sr, Y, Zr, Nb, Mo, Te, and Ru.

[0017] Preferably, the doping element B includes at least one of Ti, K, Ca, Sc, V, Rb, Sr, Y, Zr, Nb, Mo, Te, and Ru.

[0018] The doping elements A and B listed above can effectively produce favorable lattice defects or widen the diffusion channels of Li ions, thereby improving the diffusion kinetics of Li ions in the lattice, improving the ionic conductivity or electronic conductivity of the material, and further improving the electrochemical properties of the material.

[0019] Preferably, the particle size distribution of the positive electrode material is: 0.1-0.3 μm accounts for 40% by mass, 0.3-0.5 μm accounts for 20% by mass, 0.5-1 μm accounts for 20% by mass, 1-1.5 μm accounts for 10% by mass, and 1.5-2 μm accounts for 10% by mass.

[0020] Preferably, in the nickel-cobalt-manganese-aluminum quaternary positive electrode material, the doping amount of the doping element A is 200-6000ppm; in the lithium iron phosphate positive electrode material, the doping amount of the doping element B is 200-6000ppm%. Controlling the doping amount of the doping element in the nickel-cobalt-manganese-aluminum quaternary positive electrode material and the lithium iron phosphate positive electrode material within a certain numerical range can effectively produce a certain amount of lattice defects and widen the lithium ion diffusion channel, improve the lithium ion transmission efficiency and conductivity, and then effectively improve the electrochemical properties of the positive electrode material after the two materials are compounded, such as ion conductivity and conductivity. If the doping element is too little, the effect of improving the electrochemical properties of the positive electrode material such as ion conductivity and conductivity is not obvious, and if the doping element is too much, it may bring about unfavorable lattice defects, deteriorate the stability of the crystal structure of the positive electrode material, and deteriorate the electrochemical properties of the material.

[0021] Preferably, in the nickel-cobalt-manganese-aluminum quaternary positive electrode material, the doping amount of the doping element A is 1500 to 4000 ppm.

[0022] Preferably, in the lithium iron phosphate positive electrode material, the doping amount of the doping element B is 1000 to 3500 ppm.

[0023] Preferably, the doping element A is consistent with the doping element B. Keeping the types of doping elements in the nickel-cobalt-manganese-aluminum quaternary positive electrode material and the lithium iron phosphate positive electrode material consistent is more conducive to improving the ion and electron conductivity of the compounded positive electrode material, because the same doping element is smoother in the lithium ion transmission and electron transmission process, which is more conducive to improving the electrochemical performance of the compounded positive electrode material.

[0024] Preferably, doping element A and doping element B independently include Ti, K, and Nb; or doping element A and doping element B independently include Ca, Sr, and Zr. Ti, K, and Nb can replace Li, Fe, and O in LFP, can produce more favorable lattice defects, and are more conducive to Li ion diffusion channels, and the combination of these doping elements has a more obvious effect on improving the electrochemical properties of the composite positive electrode material, so it can effectively optimize the battery performance. Ca, Sr, and Zr can replace Li, Fe, and O in LFP, can produce more favorable lattice defects, and are more conducive to Li ion diffusion channels, and the combination of these doping elements has a more obvious effect on improving the electrochemical properties of the composite positive electrode material, so it can effectively optimize the battery performance.

[0025] According to the second aspect of the present invention, a method for preparing the above-mentioned positive electrode material is provided, comprising the following steps: S1. Mixing the nickel-cobalt-manganese-aluminum quaternary positive electrode material and the lithium iron phosphate positive electrode material in water, and grinding the particle size in the mixed system to 1 to 10 μm to obtain a slurry; S2. Spray drying the slurry at a drying temperature of 90 to 100°C, and controlling the particle size of the particles after drying to 5 to 20 μm; S3. Then, air flow milling and mechanical milling are performed in sequence to obtain the positive electrode material. Under the above-mentioned preparation method, the mixing effect of the nickel-cobalt-manganese-aluminum quaternary positive electrode material and the lithium iron phosphate positive electrode material is higher, which can enable smoother transmission during the charge and discharge cycle. At the same time, due to the better mixing effect, the compounded positive electrode material also has a higher conductivity and powder compaction density, thereby effectively improving the energy density, capacity and fast charging performance of the positive electrode material.

[0026] Preferably, in S1, during the grinding process, the size of the zirconium balls used is 3-8 μm, and the volume filling ratio is 50-80%.

[0027] Preferably, in S1, grinding is performed using a fine grinder.

[0028] Preferably, in S3, the specific conditions of airflow milling are: bearing protection gas is above 450mbar, gap protection gas is above 350mbar, classifying wheel speed is 1000-2000rpm, grinding air pressure is 2-5bar, and material weight is 250kg-650kg; the specific conditions of mechanical milling are: feed particle size is 10-20μm, spindle speed is 800-1500rpm, motor power is 500-900kW, and charging amount is 400-500kg. Under the above-mentioned airflow milling and mechanical milling conditions, the particle size and particle size distribution of the positive electrode material can be controlled within a certain range, which is conducive to the consideration of the compaction density, energy density, cycle performance, and safety performance of the positive electrode material.

[0029] Preferably, the jet mill pulverizes using a CGS jet mill.

[0030] Preferably, the mechanical milling uses an ALPA mechanical milling machine.

[0031] Preferably, in S3, after the air flow milling and mechanical milling, screening is also required. The purpose of screening is to remove oversized particles to prevent them from affecting the overall performance of the particles.

[0032] Preferably, in S1, the preparation method of the nickel-cobalt-manganese-aluminum quaternary positive electrode material includes the following steps: a1. Mix a first lithium source, a nickel source, a cobalt source, and a manganese source in water, and react at 70-100°C for 5-10 hours to obtain a first mixed system; a2. Cool the first mixed system to 50-60°C, then add a first carbon source and a doping element A source thereto, and react at 50-60°C for 4-5 hours to obtain a second mixed system; a3. Add acid to the second mixed system to adjust the pH to 3-6, and grind the particles to a particle size of 5-10 μm to obtain a third mixed system; a4. Dry the third mixed system to remove moisture, and calcine it to obtain a nickel-cobalt-manganese-aluminum quaternary positive electrode material.

[0033] Preferably, in a1, the mass ratio of the first lithium source, the nickel source, the cobalt source and the manganese source is (1-3): (2-6): (1-3): (2-4): (1-5).

[0034] Preferably, the first lithium source comprises lithium nitrate; the nickel source comprises hydrated nickel carbonate; the cobalt source comprises hydrated cobalt nitrate; and the manganese source comprises hydrated manganese acetate.

[0035] Preferably, in a2, the added amounts of the carbon source and the doping element A source are calculated based on the mass proportions of the carbon source and the doping element A source in the second mixed system being 6-9% and 1-3%, respectively.

[0036] Preferably, in a2, the first carbon source includes glucose and polyethylene glycol (PEG), and the feed mass ratio of glucose and polyethylene glycol is (4-6): (2-3); the doping element A source includes an A compound containing the doping element A.

[0037] Preferably, in a3, the amount of acid added is calculated based on the mass proportion of the acid in the third mixed system being 8 to 11%.

[0038] Preferably, in a3, the acid includes nitric acid, acetic acid and acrylic acid, and the feed mass ratio of nitric acid, acetic acid and acrylic acid is (1-3): (1.5-2.6): (5.5-6.4).

[0039] Preferably, in a3, a fine grinder is used for grinding, and the zirconium balls used have a size of 1 to 15 μm and a volume filling ratio of 80 to 90%.

[0040] Preferably, in a4, the calcination process is divided into 6 intervals, interval 1: temperature: 100-150°C, insulation time 1-2h; interval 2: temperature 200-280°C, insulation time 1.5-2.5h; interval 3: temperature 400-600°C, insulation time 0.5-1.5h; interval 4: temperature 700-800°C; insulation time 4-8h; interval 5: temperature 150-350°C, insulation time 0.5-1h; interval 6: temperature 50-100°C, insulation time 2-3h; then cool to room temperature.

[0041] Preferably, in a4, a kiln is used for calcination, and the length of the kiln is 70 to 80 m.

[0042] Preferably, in S1, the preparation method of lithium iron phosphate positive electrode material includes the following steps: b1. Mixing a ferrophosphorus source, a second lithium source, and a second carbon source in water for 2 to 5 hours to obtain a first mixture; b2. Adding a doping element B source to the first mixture and continuing to mix for 0.5 to 1 hour, and grinding the particles to a particle size of 30 to 50 μm to obtain a second mixture; b3. Spray drying the second mixture, controlling the particle size to 20 to 30 μm after drying, and then calcining to obtain a lithium iron phosphate positive electrode material.

[0043] Preferably, in b1, the mass ratio of the ferrophosphorus source, the second lithium source and the second carbon source is (6.5-7.2):(1.0-1.8):(0.3-1.5).

[0044] Preferably, the phosphate source includes iron phosphate; the second lithium source includes lithium carbonate; the second carbon source includes glucose and polyethylene glycol (PEG), and the feed mass ratio of glucose to polyethylene glycol is (0.2-1.0): (0.1-0.5).

[0045] Preferably, in b2, the amount of the doping element B source added is calculated based on the mass proportion of the doping element B source in the second mixture being 3-8%.

[0046] Preferably, the doping element B source includes a B compound containing the doping element B.

[0047] Preferably, in b2, a coarse grinder or a fine grinder is used for grinding, and the zirconium balls used have a size of 1 to 15 μm and a volume filling ratio of 60 to 85%.

[0048] Preferably, in b3, the calcination process is divided into 5 intervals, interval 1: temperature 100-200°C, insulation time 0.5-2h; interval 2: temperature 300-500°C, insulation time 1-2h; interval 3: temperature 500-800°C, insulation time 6-8h; interval 4: temperature 300-400°C, insulation time 2-3h; interval 5: temperature 50-100°C, insulation time 2-3h; and then cool to room temperature.

[0049] Preferably, in b3, a kiln is used for calcination, and the length of the kiln is 60 to 80 m.

[0050] According to a third aspect of the present invention, there is provided a positive electrode sheet comprising the above positive electrode material. The positive electrode sheet made using the above positive electrode material has a high compaction density and excellent ion and electron conductivity, and can maintain a stable structure of the positive electrode sheet after multiple charge and discharge cycles.

[0051] According to a fourth aspect of the present invention, there is provided a battery comprising the above-mentioned positive electrode sheet, wherein the compaction density of the positive electrode sheet is 3.2 to 4.2 g / cm 3 The battery prepared using the above-mentioned positive electrode sheet has high structural stability, high compaction density, and excellent ion and electron conductivity, so that the battery has high energy density, high safety performance and excellent fast charging performance. DETAILED DESCRIPTION

[0052] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.

[0053] Example 1

[0054] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0055] The nickel-cobalt-manganese-aluminum quaternary positive electrode material (NCMA) of this embodiment is prepared according to the following steps:

[0056] a1. Mix lithium nitrate, hydrated nickel carbonate, hydrated cobalt nitrate and hydrated manganese acetate in water, and react at 85°C for 8 hours to obtain a first mixed system; the mass ratio of lithium nitrate, hydrated nickel carbonate, hydrated cobalt nitrate and hydrated manganese acetate is (1-2): (4-6): (2-3): (1-3): (2-4);

[0057] a2. The first mixed system was cooled to 55°C, and then glucose, polyethylene glycol (PEG), and a titanium compound were added thereto, and the mixture was kept at 55°C for 4.5 hours to obtain a second mixed system; the amount of glucose, polyethylene glycol (PEG), and a titanium compound (TiO2) added was calculated based on the mass proportions of glucose, polyethylene glycol (PEG), and a titanium compound (TiO2) in the second mixed system being 5%, 2.5%, and 2%, respectively;

[0058] a3. Acid was added to the second mixed system to adjust the pH to 4.5, and the particles were ground to a particle size of 5 to 10 μm to obtain a third mixed system; specifically, a fine grinder was used for grinding, and the zirconium ball size used was 1 to 15 μm, and the volume filling ratio was 80 to 90%;

[0059] a4. After drying and removing the water from the third mixed system, calcining is performed to obtain a nickel-cobalt-manganese-aluminum quaternary positive electrode material, whose chemical formula is Li 1.5 Ni 0.4 Mn 0.2 Co 0.2 Al 0.1 Ti 0.1 O2, and the final doping amount of titanium element (Ti) in the nickel-cobalt-manganese-aluminum quaternary positive electrode material is 2500ppm; specifically, a kiln is used for calcination, the kiln length is 70-80m, and the calcination process is divided into 6 intervals, interval 1: temperature 125℃, insulation time 1.5h; interval 2: temperature 240℃, insulation time 2h; interval 3: temperature 500℃, insulation time 1h; interval 4: temperature 750℃; insulation time 6h; interval 5: temperature 250℃, insulation time 0.75h; interval 6: temperature 75℃, insulation time 2.5h; then cool to room temperature.

[0060] (2) Preparation of lithium iron phosphate positive electrode materials

[0061] The lithium iron phosphate positive electrode material (LFP) of this embodiment is prepared according to the following steps:

[0062] b1. Mixing iron phosphate, lithium carbonate, glucose and polyethylene glycol (PEG) in water for 3.5 hours to obtain a first mixture; the mass ratio of iron phosphate, lithium carbonate, glucose and polyethylene glycol (PEG) is 6.85:1.4:0.6:0.3;

[0063] b2. Add the titanium compound (TiO2) to the first mixture and continue mixing for 0.75h, and grind the particles to a particle size of 30 to 50 μm to obtain a second mixture; the amount of the titanium compound added is calculated to be 5.5% by mass of the titanium compound in the second mixture; specifically, a coarse grinder or a fine grinder is used for grinding, and the zirconium ball size used is 1 to 15 μm, and the volume filling ratio is 60 to 85%;

[0064] b3. The second mixture is spray dried, and the particle size is controlled to be 20 to 30 μm after drying, and then calcined to obtain a lithium iron phosphate positive electrode material, whose chemical formula is Li 1.5 Fe(PO4) 1.5 Ti 0.3 , and the final doping amount of titanium element (Ti) in the lithium iron phosphate positive electrode material is 2000ppm; specifically, a kiln is used for calcination, the kiln length is 60 to 80m, and the calcination process is divided into 5 intervals, interval 1: temperature 150°C, insulation time 1.2h; interval 2: temperature 400°C, insulation time 1.5h; interval 3: temperature 750°C, insulation time 7.5h; interval 4: temperature 350°C, insulation time 2.5h; interval 5: temperature 75°C, insulation time 2.5h; then cool to room temperature.

[0065] (3) Preparation of positive electrode materials

[0066] The positive electrode material of this embodiment is prepared according to the following steps:

[0067] S1. The nickel-cobalt-manganese-aluminum quaternary positive electrode material and the lithium iron phosphate positive electrode material prepared above are mixed in water, and the particle size of the particles in the mixed system is ground to 1 to 10 μm to obtain a slurry; the mass ratio of the nickel-cobalt-manganese-aluminum quaternary positive electrode material to the lithium iron phosphate positive electrode material is 2.5:7.5; the grinding is specifically carried out using a fine grinder, the size of the zirconium balls used is 3 to 8 μm, and the volume filling ratio is 50 to 80%;

[0068] S2. The slurry is spray dried at a drying temperature of 90 to 100°C, and the particle size after drying is controlled to be 5 to 20 μm;

[0069] S3. Then, air flow milling and mechanical milling are carried out in sequence to obtain positive electrode materials, and the particle size of the positive electrode material is 0.1-2μm, and the particle size distribution is: the mass proportion of 0.1-0.3μm is 40%, the mass proportion of 0.3-0.5μm is 20%, the mass proportion of 0.5-1μm is 20%, the mass proportion of 1-1.5μm is 10%, and the mass proportion of 1.5-2μm is 10%; the specific conditions of air flow milling are: the air flow mill adopts CGS air flow mill, the bearing protection gas is 550mbar, the gap protection gas is 500mbar, the classification wheel speed is 1600rpm, the grinding air pressure is 3bar, and the material weight is 500kg; the specific conditions of mechanical milling are: the mechanical mill adopts ALPA mechanical mill, the feed particle size is 13μm, the spindle speed is 1000rpm, the electrode power is 650kW, and the charging amount is 450kg.

[0070] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0071] ① Preparation of positive electrode sheet: The positive electrode material, positive electrode material, conductive agent 1 (SP), conductive agent 2 (CNT), and binder PVDF prepared above were added to NMP in a mass ratio of 96.9:1.6:0.5:1.2 and mixed evenly to obtain positive electrode slurry, and the positive electrode sheet was prepared with the positive electrode slurry obtained. The compacted density of the positive electrode sheet was 3.6 g / cm 3 .

[0072] ② Preparation of negative electrode sheet: Graphite, conductive agent (SP), binder 1 (CMC), and binder 2 (SBR) were added into water at a mass ratio of 96.0:0.7:1.3:2.0 and mixed to obtain negative electrode slurry, and a negative electrode sheet was prepared using the obtained negative electrode slurry.

[0073] ③ Use the above-mentioned positive electrode sheet, negative electrode sheet, 1 mol / L LiPF6 / EC+DMC+EMC (v / v=1:1:1) electrolyte, PE+alumina separator, and shell to assemble the soft-pack battery using conventional production processes.

[0074] Example 2

[0075] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0076] The preparation of the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this embodiment is consistent with that in Example 1.

[0077] (2) Preparation of lithium iron phosphate positive electrode materials

[0078] The preparation of the lithium iron phosphate positive electrode material in this embodiment is consistent with that in Example 1.

[0079] (3) Preparation of positive electrode materials

[0080] In the process of preparing the positive electrode material in this embodiment, the difference from that in embodiment 1 is that in S1, the mass ratio of the nickel-cobalt-manganese-aluminum quaternary positive electrode material to the lithium iron phosphate positive electrode material is 0.5:9.5. The rest of the operations are consistent with the embodiment.

[0081] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0082] The preparation of the positive electrode sheet, negative electrode sheet and battery in this embodiment is consistent with that in Embodiment 1.

[0083] Example 3

[0084] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0085] The preparation of the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this embodiment is consistent with that in Example 1.

[0086] (2) Preparation of lithium iron phosphate positive electrode materials

[0087] The preparation of the lithium iron phosphate positive electrode material in this embodiment is consistent with that in Example 1.

[0088] (3) Preparation of positive electrode materials

[0089] In the process of preparing the positive electrode material in this embodiment, the difference from that in embodiment 1 is that in S1, the mass ratio of the nickel-cobalt-manganese-aluminum quaternary positive electrode material to the lithium iron phosphate positive electrode material is 7.0:3.0. The rest of the operations are consistent with the embodiment.

[0090] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0091] The preparation of the positive electrode sheet, negative electrode sheet and battery in this embodiment is consistent with that in Embodiment 1.

[0092] Example 4

[0093] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0094] The preparation of the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this embodiment is consistent with that in Example 1.

[0095] (2) Preparation of lithium iron phosphate positive electrode materials

[0096] The preparation of the lithium iron phosphate positive electrode material in this embodiment is consistent with that in Example 1.

[0097] (3) Preparation of positive electrode materials

[0098] In the process of preparing the positive electrode material in this embodiment, the difference from that in embodiment 1 is that in S1, the mass ratio of the nickel-cobalt-manganese-aluminum quaternary positive electrode material to the lithium iron phosphate positive electrode material is 1:9. The rest of the operations are consistent with those in the embodiment.

[0099] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0100] The preparation of the positive electrode sheet, negative electrode sheet and battery in this embodiment is consistent with that in Embodiment 1.

[0101] Example 5

[0102] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0103] The preparation of the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this embodiment is consistent with that in Example 1.

[0104] (2) Preparation of lithium iron phosphate positive electrode materials

[0105] The preparation of the lithium iron phosphate positive electrode material in this embodiment is consistent with that in Example 1.

[0106] (3) Preparation of positive electrode materials

[0107] The process of preparing the positive electrode material in this embodiment is different from that in Embodiment 1 in that in S1, the mass ratio of the nickel-cobalt-manganese-aluminum quaternary positive electrode material to the lithium iron phosphate positive electrode material is 4:6. The remaining operations are consistent with the embodiment.

[0108] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0109] The preparation of the positive electrode sheet, negative electrode sheet and battery in this embodiment is consistent with that in Embodiment 1.

[0110] Example 6

[0111] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0112] The preparation of the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this embodiment is consistent with that in Example 1.

[0113] (2) Preparation of lithium iron phosphate positive electrode materials

[0114] The preparation of the lithium iron phosphate positive electrode material in this embodiment is consistent with that in Example 1.

[0115] (3) Preparation of positive electrode materials

[0116] In the process of preparing the positive electrode material in this embodiment, the difference from Example 1 is that in S3, the specific conditions of airflow milling and mechanical milling are regulated so that the particle size distribution of the final positive electrode material is: 0.1-0.3 μm accounts for 30% by mass, 0.3-0.5 μm accounts for 25% by mass, 0.5-1 μm accounts for 20% by mass, 1-1.5 μm accounts for 15% by mass, and 1.5-2 μm accounts for 10% by mass; wherein, the specific conditions of airflow milling are that the airflow mill uses CGS airflow mill, the bearing protection gas is 500 mbar, the gap protection gas is 460 mbar, the classifying wheel speed is 1300 rpm, the grinding air pressure is 2 bar, and the material weight is 480 kg. The specific conditions of mechanical milling are that the mechanical mill uses ALPA mechanical mill, the feed particle size is 15 μm, the spindle speed is 1200 rpm, the motor power is 800 kW, and the loading amount is 470 kg. The rest of the operations are consistent with the embodiment.

[0117] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0118] The preparation of the positive electrode sheet, negative electrode sheet and battery in this embodiment is consistent with that in Embodiment 1.

[0119] Example 7

[0120] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0121] The preparation of the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this embodiment is consistent with that in Example 1.

[0122] (2) Preparation of lithium iron phosphate positive electrode materials

[0123] The preparation of the lithium iron phosphate positive electrode material in this embodiment is consistent with that in Example 1.

[0124] (3) Preparation of positive electrode materials

[0125] In the process of preparing the positive electrode material in this embodiment, the difference from Example 1 is that in S3, the specific conditions of airflow milling and mechanical milling are regulated so that the particle size distribution of the final positive electrode material is: 0.1-0.3 μm accounts for 50% by mass, 0.3-0.5 μm accounts for 20% by mass, 0.5-1 μm accounts for 25% by mass, 1-1.5 μm accounts for 5% by mass, and 1.5-2 μm accounts for 10% by mass; wherein, the specific conditions of airflow milling are that the airflow mill uses CGS airflow mill, bearing protection gas is 600 mbar, gap protection gas is 530 mbar, classifying wheel speed is 1800 rpm, grinding air pressure is 4 bar, and material weight is 550 kg, and the specific conditions of mechanical milling are that the mechanical mill uses ALPA mechanical mill, feed particle size is 13 μm, spindle speed is 1000 rpm, motor power is 650 kW, and charging amount is 430 kg. The rest of the operations are consistent with the embodiment.

[0126] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0127] The preparation of the positive electrode sheet, negative electrode sheet and battery in this embodiment is consistent with that in Embodiment 1.

[0128] Example 8

[0129] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0130] In the process of preparing the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this embodiment, the difference from that in embodiment 1 is that in a2, the amount of titanium compound added is regulated so that the final doping amount of titanium element (Ti) in the nickel-cobalt-manganese-aluminum quaternary positive electrode material is 200 ppm. The rest of the operations are the same as in embodiment 1.

[0131] (2) Preparation of lithium iron phosphate positive electrode materials

[0132] The preparation of the lithium iron phosphate positive electrode material in this embodiment is consistent with that in Example 1.

[0133] (3) Preparation of positive electrode materials

[0134] The preparation of the positive electrode material in this example is consistent with that in Example 1.

[0135] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0136] The preparation of the positive electrode sheet, negative electrode sheet and battery in this embodiment is consistent with that in Embodiment 1.

[0137] Example 9

[0138] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0139] In the process of preparing the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this embodiment, the difference from that in embodiment 1 is that in a2, the amount of titanium compound added is regulated so that the final doping amount of titanium element (Ti) in the nickel-cobalt-manganese-aluminum quaternary positive electrode material is 1500 ppm. The rest of the operations are the same as in embodiment 1.

[0140] (2) Preparation of lithium iron phosphate positive electrode materials

[0141] The preparation of the lithium iron phosphate positive electrode material in this embodiment is consistent with that in Example 1.

[0142] (3) Preparation of positive electrode materials

[0143] The preparation of the positive electrode material in this example is consistent with that in Example 1.

[0144] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0145] The preparation of the positive electrode sheet, negative electrode sheet and battery in this embodiment is consistent with that in Embodiment 1.

[0146] Example 10

[0147] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0148] In the process of preparing the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this embodiment, the difference from that in embodiment 1 is that in a2, the amount of titanium compound added is regulated so that the final doping amount of titanium element (Ti) in the nickel-cobalt-manganese-aluminum quaternary positive electrode material is 1500 ppm. The rest of the operations are the same as in embodiment 1.

[0149] (2) Preparation of lithium iron phosphate positive electrode materials

[0150] The preparation of the lithium iron phosphate positive electrode material in this embodiment is consistent with that in Example 1.

[0151] (3) Preparation of positive electrode materials

[0152] The preparation of the positive electrode material in this example is consistent with that in Example 1.

[0153] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0154] The preparation of the positive electrode sheet, negative electrode sheet and battery in this embodiment is consistent with that in Embodiment 1.

[0155] Embodiment 11

[0156] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0157] The preparation of the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this embodiment is consistent with that in Example 1.

[0158] (2) Preparation of lithium iron phosphate positive electrode materials

[0159] In the process of preparing the lithium iron phosphate positive electrode material in this embodiment, the difference from Example 1 is that in b2, the amount of the titanium compound added is regulated and the amount of the titanium compound added is calculated so that the final mass proportion of the titanium element (Ti) in the lithium iron phosphate positive electrode material is 6000ppm. The rest of the operations are the same as in Example 1.

[0160] (3) Preparation of positive electrode materials

[0161] The preparation of the positive electrode material in this example is consistent with that in Example 1.

[0162] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0163] The preparation of the positive electrode sheet, negative electrode sheet and battery in this embodiment is consistent with that in Embodiment 1.

[0164] Example 12

[0165] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0166] In the process of preparing the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this embodiment, the difference from embodiment 1 is that in a2, the titanium compound is replaced by a calcium compound (CaCO3), and the chemical formula of the nickel-cobalt-manganese-aluminum quaternary positive electrode material is Li 1..5 Ni 0.3 Mn 0. 2Co 0.2 Al 0.1 Ca 0.2 The remaining operations are the same as those in Example 1.

[0167] (2) Preparation of lithium iron phosphate positive electrode materials

[0168] In the process of preparing the lithium iron phosphate positive electrode material in this embodiment, the difference from embodiment 1 is that in b2, the titanium compound is replaced by a calcium compound (CaCO3), and the chemical formula of the lithium iron phosphate positive electrode material is Li 1.5 Fe(PO4) 1.5 Ca 0.6 The remaining operations are consistent with those in Example 1.

[0169] (3) Preparation of positive electrode materials

[0170] The preparation of the positive electrode material in this example is consistent with that in Example 1.

[0171] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0172] The preparation of the positive electrode sheet, negative electrode sheet and battery in this embodiment is consistent with that in Embodiment 1.

[0173] Embodiment 13

[0174] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0175] In the process of preparing the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this embodiment, the difference from embodiment 1 is that in a2, the titanium compound is replaced by a Sc compound (Sc2O3), and the chemical formula of the nickel-cobalt-manganese-aluminum quaternary positive electrode material is Li 1..5 Ni 0.36 Mn 0.2 Co 0.2 Al 0.1 Sc 0.14 The remaining operations are the same as those in Example 1.

[0176] (2) Preparation of lithium iron phosphate positive electrode materials

[0177] In the process of preparing the lithium iron phosphate positive electrode material in this embodiment, the difference from embodiment 1 is that in b2, the titanium compound is replaced by a Sc compound (Sc2O3), and the chemical formula of the lithium iron phosphate positive electrode material is Li 1.5 Fe(PO4) 1.5 Sc 0.4 The remaining operations are consistent with those in Example 1.

[0178] (3) Preparation of positive electrode materials

[0179] The preparation of the positive electrode material in this example is consistent with that in Example 1.

[0180] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0181] The preparation of the positive electrode sheet, negative electrode sheet and battery in this embodiment is consistent with that in Embodiment 1.

[0182] Embodiment 14

[0183] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0184] In the process of preparing the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this embodiment, the difference from embodiment 1 is that in a2, the titanium compound is replaced by a V compound (VO2), and the chemical formula of the nickel-cobalt-manganese-aluminum quaternary positive electrode material is Li 1.5 Ni 0.4 Mn 0.2 Co 0.2 Al 0.1 V 0.1 The remaining operations are the same as those in Example 1.

[0185] (2) Preparation of lithium iron phosphate positive electrode materials

[0186] In the process of preparing the lithium iron phosphate positive electrode material in this embodiment, the difference from embodiment 1 is that in b2, the titanium compound is replaced by a V compound (VO2), and the chemical formula of the lithium iron phosphate positive electrode material is Li 1.5 Fe(PO4) 1.5 V 0.3 The remaining operations are consistent with those in Example 1.

[0187] (3) Preparation of positive electrode materials

[0188] The preparation of the positive electrode material in this example is consistent with that in Example 1.

[0189] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0190] The preparation of the positive electrode sheet, negative electrode sheet and battery in this embodiment is consistent with that in Embodiment 1.

[0191] Embodiment 15

[0192] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0193] In the process of preparing the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this embodiment, the difference from embodiment 1 is that in a2, the titanium compound is replaced by a mixture of a Ti compound (TiO2), a K compound (K2CO3), and a Nb compound (Nb2O5), and by adjusting the amount of the Ti compound, the K compound, and the Nb compound, the chemical formula of the nickel-cobalt-manganese-aluminum quaternary positive electrode material is Li 1.5 Ni 0.4 2Mn 0.2 Co 0.2 Al 0.1 A 0.08 O2, A includes Ti, K, and Nb elements, and the molar ratio of Ti, K, and Nb is 6:1:3. The remaining operations are consistent with those in Example 1.

[0194] (2) Preparation of lithium iron phosphate positive electrode materials

[0195] In the process of preparing the lithium iron phosphate positive electrode material in this embodiment, the difference from embodiment 1 is that in b2, the titanium compound is replaced by a mixture of a Ti compound (TiO2), a K compound (K2CO3), and a Nb compound (Nb2O5), and the chemical formula of the lithium iron phosphate positive electrode material is Li 1.5 Fe(PO4) 1.5 B 0.25 , B includes Ti, K, and Nb elements, and the molar ratio of Ti, K, and Nb is 6:1:3. The remaining operations are consistent with those in Example 1.

[0196] (3) Preparation of positive electrode materials

[0197] The preparation of the positive electrode material in this example is consistent with that in Example 1.

[0198] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0199] The preparation of the positive electrode sheet, negative electrode sheet and battery in this embodiment is consistent with that in Embodiment 1.

[0200] Example 16

[0201] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0202] In the process of preparing the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this embodiment, the difference from embodiment 1 is that in a2, the titanium compound is replaced by a mixture of a Ca compound (CaCO3), a Sr compound (SrO), and a Zr compound (ZrO2), and by controlling the amount of the Ca compound, the Sr compound, and the Zr compound, the chemical formula of the nickel-cobalt-manganese-aluminum quaternary positive electrode material is Li 1.5 Ni 0.43 Mn 0.2 Co 0.2 Al 0.1 A 0.07 O2, A includes Ca, Sr, and Zr elements, and the molar ratio of Ca, Sr, and Zr is 4:3:3. The remaining operations are consistent with those in Example 1.

[0203] (2) Preparation of lithium iron phosphate positive electrode materials

[0204] In the process of preparing the lithium iron phosphate positive electrode material in this embodiment, the difference from embodiment 1 is that in b2, the titanium compound is replaced by a mixture of a Ca compound (CaCO3), a Sr compound (SrO), and a Zr compound (ZrO2), and by controlling the amount of the Ca compound, the Sr compound, and the Zr compound, the chemical formula of the lithium iron phosphate positive electrode material is Li 1.5 Fe(PO4) 1.5 B 0.2 , A includes Ca, Sr, and Zr elements, and the molar ratio of Ca, Sr, and Zr is 5:2:3. The remaining operations are consistent with those in Example 1.

[0205] (3) Preparation of positive electrode materials

[0206] The preparation of the positive electrode material in this example is consistent with that in Example 1.

[0207] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0208] The preparation of the positive electrode sheet, negative electrode sheet and battery in this embodiment is consistent with that in Embodiment 1.

[0209] Embodiment 17

[0210] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0211] The preparation of the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this embodiment is consistent with that in Example 1.

[0212] (2) Preparation of lithium iron phosphate positive electrode materials

[0213] In the process of preparing the lithium iron phosphate positive electrode material in this embodiment, the difference from that in embodiment 1 is that in b2, the titanium compound is replaced by a Y compound (Y2O3), and the chemical formula of the lithium iron phosphate positive electrode material is Li 1.5 Fe(PO4) 1.5 Y 0.16 The remaining operations are consistent with those in Example 1.

[0214] (3) Preparation of positive electrode materials

[0215] The preparation of the positive electrode material in this example is consistent with that in Example 1.

[0216] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0217] The preparation of the positive electrode sheet, negative electrode sheet and battery in this embodiment is consistent with that in Embodiment 1.

[0218] Embodiment 18

[0219] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0220] In the process of preparing the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this embodiment, the difference from embodiment 1 is that in a2, the titanium compound is replaced by a Mg compound (MgO), and the chemical formula of the nickel-cobalt-manganese-aluminum quaternary positive electrode material is Li 1.5 Ni 0.3 Mn 0.2 Co 0.2 Al 0.1 Mg 0.2 The remaining operations are the same as those in Example 1.

[0221] (2) Preparation of lithium iron phosphate positive electrode materials

[0222] In the process of preparing the lithium iron phosphate positive electrode material in this embodiment, the difference from the embodiment 1 is that in b2, the titanium compound is replaced by the Mg compound (MgO), and the chemical formula of the lithium iron phosphate positive electrode material is i 1.5 Fe(PO4) 1.5 Mg 0.8 The remaining operations are consistent with those in Example 1.

[0223] (3) Preparation of positive electrode materials

[0224] The preparation method of the positive electrode material in this comparative example is the same as that in Example 1.

[0225] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0226] The preparation of the positive electrode sheet, negative electrode sheet and battery in this comparative example is consistent with that in Example 1.

[0227] Comparative Example 1

[0228] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0229] The preparation of the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this comparative example is consistent with that in Example 1.

[0230] (2) Preparation of lithium iron phosphate positive electrode materials

[0231] The preparation of the lithium iron phosphate positive electrode material in this comparative example is consistent with that in Example 1.

[0232] (3) Preparation of positive electrode materials

[0233] In the process of preparing the positive electrode material in this comparative example, the difference from Example 1 is that in S1, the mass ratio of the nickel-cobalt-manganese-aluminum quaternary positive electrode material to the lithium iron phosphate positive electrode material is 0.3:9.7. The rest of the operations are consistent with the example.

[0234] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0235] The preparation of the positive electrode sheet, negative electrode sheet and battery in this comparative example is consistent with that in Example 1.

[0236] Comparative Example 2

[0237] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0238] The preparation of the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this comparative example is consistent with that in Example 1.

[0239] (2) Preparation of lithium iron phosphate positive electrode materials

[0240] The preparation of the lithium iron phosphate positive electrode material in this comparative example is consistent with that in Example 1.

[0241] (3) Preparation of positive electrode materials

[0242] In the process of preparing the positive electrode material in this comparative example, the difference from Example 1 is that in S1, the mass ratio of the nickel-cobalt-manganese-aluminum quaternary positive electrode material to the lithium iron phosphate positive electrode material is 8:2. The rest of the operations are consistent with the example.

[0243] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0244] The preparation of the positive electrode sheet, negative electrode sheet and battery in this comparative example is consistent with that in Example 1.

[0245] Comparative Example 3

[0246] (1) Preparation of nickel-cobalt-manganese-aluminum quaternary positive electrode materials

[0247] The preparation of the nickel-cobalt-manganese-aluminum quaternary positive electrode material in this comparative example is consistent with that in Example 1.

[0248] (2) Preparation of lithium iron phosphate positive electrode materials

[0249] The preparation of the lithium iron phosphate positive electrode material in this comparative example is consistent with that in Example 1.

[0250] (3) Preparation of positive electrode materials

[0251] In the process of preparing the positive electrode material in this comparative example, the difference from Example 1 is that the operations S1 and S2 are not performed, that is, wet grinding and mixing are not performed, but dry mixing and grinding to 5-20 μm are performed directly, and then the air flow milling and mechanical milling operations in S3 are performed. The remaining operations are consistent with the example.

[0252] (4) Preparation of positive electrode sheet, negative electrode sheet and battery

[0253] The preparation of the positive electrode sheet, negative electrode sheet and battery in this comparative example is consistent with that in Example 1.

[0254] Test Case

[0255] 1. Experimental Construction Method

[0256] The batteries prepared in all the above embodiments and comparative examples were tested for energy density, capacity, cycle capacity retention rate, and fast charging performance. The specific testing methods are as follows:

[0257] (1) Energy density: a) The battery is discharged at a constant current of 0.5C to 2.5V; b) Let it stand for 5 minutes; c) The battery is charged at a constant current and constant voltage of 0.5C, with a cut-off voltage of 3.65V and a cut-off current of 0.05C; d) Let it stand for 5 minutes; e) The battery is discharged at a constant current of 0.5C to 2.5V; f) Repeat steps b) to e) 13 times; The energy density is calculated based on the last discharge capacity: Energy density = (capacity * voltage) / mass (here is mass energy density).

[0258] (2) Capacity: a) The battery was discharged at a constant current of 0.5C to 2.5V; b) it was left to stand for 5 minutes; c) the battery was charged at a constant current and constant voltage of 0.5C, with a cut-off voltage of 3.65V and a cut-off current of 0.05C; d) it was left to stand for 5 minutes; e) the battery was discharged at a constant current of 0.5C to 2.5V; f) steps b) to e) were repeated 13 times; the last discharge capacity was taken as the battery capacity.

[0259] (3) Cycle capacity retention rate: a) Place the battery under the corresponding temperature conditions for 4 to 6 hours; b) Discharge the battery to 2.5V at a constant current of 0.5C; c) Let it stand for 5 minutes; d) Charge the battery at a constant current and constant voltage of 0.5C, with a cut-off voltage of 3.65V and a cut-off current of 0.05C; e) Let it stand for 5 minutes; f) Discharge the battery to 2.5V at a constant current of 0.5C; g) Repeat steps b) to e) 3 times, and record the last discharge capacity as the battery capacity Q0; h) Let it stand for 5 minutes; i) Charge the battery at a constant current and constant voltage corresponding to 0.5Q0 until the battery voltage reaches 3.65V, with a cut-off current of 0.05C, and let it stand for 5 minutes; j) Discharge the battery to 2.5V at a constant current corresponding to Q0; k) Start step h, cycle N times; Capacity retention rate / % = discharge capacity of the Nth cycle / maximum discharge capacity*100. This experiment tests the capacity retention rate after 15,000 cycles.

[0260] (4) Fast charging performance (5C full charge time): a) The battery is discharged at a constant current of 0.5C to 2.5V; b) Let it stand for 5 minutes; c) The battery is charged at a constant current and constant voltage of 0.5C, with a cut-off voltage of 3.65V and a cut-off current of 0.05C; d) Let it stand for 5 minutes; e) The battery is discharged at a constant current of 0.5C to 2.5V; f) Repeat steps b) to e) 3 times, record the last discharge capacity as the battery capacity Q0, and charge at a constant current and constant voltage corresponding to 0.01 to 0.1Q, with a cut-off voltage of 2.7V; g) Let it stand for 5 minutes; h) Charge at a constant current and constant voltage of 5C, with a cut-off voltage of 3.65V, and then charge at a constant voltage with a cut-off current of 0.05C; calculate the time it takes for the voltage to change from 2.5V to 3.65V, which is the fast full charge time of the battery.

[0261] 2. Experimental results

[0262] The test results of the energy density, capacity, cycle capacity retention rate and fast charging performance of the batteries prepared in all the above embodiments and comparative examples are shown in Table 1.

[0263] Table 1 Test results of battery performance prepared in the examples and comparative examples

[0264]

[0265]

[0266] It can be seen from Table 1 that the battery prepared with the positive electrode material provided by the present invention has high energy density, capacity and cycle capacity retention rate, and can be fully charged in a short time at a high rate, and has good comprehensive performance. In particular, the positive electrode material provided by the present invention is a composite positive electrode material of a nickel-cobalt-manganese-aluminum quaternary positive electrode material and a lithium iron phosphate positive electrode material, which are used in a specific mass ratio, and the nickel-cobalt-manganese-aluminum quaternary positive electrode material and the lithium iron phosphate positive electrode material are both doped with other metal elements, which effectively improves the energy density, capacity, cycle capacity retention rate and fast charging performance of the lithium iron phosphate positive electrode material. Please refer to Examples 1 to 18 for details.

[0267] In Comparative Example 1 and Comparative Example 2, the mass ratio of the nickel-cobalt-manganese-aluminum quaternary positive electrode material and the lithium iron phosphate positive electrode material is not in the range of (0.3-5.0): (7.0-9.5), which leads to a decrease in the composite effect of the two materials, that is, the synergistic effect of the two materials decreases, resulting in a decrease in the ionic conductivity or electronic conductivity of the final positive electrode material, reducing the electrochemical properties of the positive electrode material, and resulting in a decrease in the energy density, capacity, cycle capacity retention rate and fast charging performance of the battery.

[0268] In Comparative Example 3, during mixing, S1 and S2 operations are not performed, that is, wet grinding and mixing are not performed, and dry mixing is directly ground to 5-20 μm, and then air flow milling and mechanical milling are performed in sequence. This will cause the mixing effect of the nickel-cobalt-manganese-aluminum quaternary positive electrode material and the lithium iron phosphate positive electrode material to deteriorate, resulting in a decrease in the electrochemical properties of the final positive electrode material in various aspects, thereby causing degradation of various aspects of the battery performance.

[0269] Further comparing Example 1 with Examples 2 to 5, although in Examples 1 to 5, the mass ratios of the nickel-cobalt-manganese-aluminum quaternary positive electrode material and the lithium iron phosphate positive electrode material are all in the range of (0.3 to 5.0): (7.0 to 9.5), the different mass ratios of the two materials within this range will still have a certain impact on the performance of the positive electrode material. When the mass ratio of the nickel-cobalt-manganese-aluminum quaternary positive electrode material and the lithium iron phosphate positive electrode material is in the range of (1 to 4): (6 to 9), the two materials have better synergistic effect, especially when the mass ratio is 2.5:7.5, the synergistic effect of the two materials is best, and the battery has the best electrochemical performance.

[0270] Comparing Example 1 with Examples 6-7, in Examples 6-7, the particle size distribution of the final positive electrode material is different from that in Example 1, which also causes the performance of the battery prepared by the positive electrode material to be different, which shows that the particle size distribution of the positive electrode material has a certain influence on the electrochemical performance of the battery. And it can be seen from Examples 1 and 6-7 that when the particle size distribution of the positive electrode material satisfies that the mass proportion of 0.1-0.3μm is 40%, the mass proportion of 0.3-0.5μm is 20%, the mass proportion of 0.5-1μm is 20%, the mass proportion of 1-1.5μm is 10%, and the mass proportion of 1.5-2μm is 10%, the battery has the best performance in all aspects, that is, such a particle size distribution is more conducive to battery performance.

[0271] Comparing Example 1 with Examples 8 to 11, the doping element A in the nickel-cobalt-manganese-aluminum quaternary positive electrode material in Example 8 is less, and the doping element B in the lithium iron phosphate positive electrode material in Example 11 is more, which also causes the battery performance to be lower than that of Examples 1, 9, and 10. This shows that controlling the content of the doping element A in the nickel-cobalt-manganese-aluminum quaternary positive electrode material and the doping element B in the lithium iron phosphate positive electrode material within a certain range is more conducive to the modification of these doping elements on the nickel-cobalt-manganese-aluminum quaternary positive electrode material and the lithium iron phosphate positive electrode material, thereby further improving the performance of the final positive electrode material, and further improving the various aspects of the battery performance.

[0272] Comparing Example 1 with Examples 12 to 18, first, specifically comparing Example 1 with Examples 12 to 14, when the nickel-cobalt-manganese-aluminum quaternary positive electrode material and the lithium iron phosphate positive electrode material are both single doping elements, the Ti element has the best improvement effect on these two materials, thereby making the relevant performance of the battery prepared by the positive electrode material the best. Second, specifically comparing Example 1 with Examples 15 to 16, the cobalt-manganese-aluminum quaternary positive electrode material and the lithium iron phosphate positive electrode material in Examples 15 and 16 are all three doping elements. Under the joint action of multiple doping elements, the performance of the positive electrode material can be improved in many aspects, such as improving the crystal stability, ion transmission ability and conductivity of the positive electrode material, thereby effectively improving the various aspects of the battery performance. Third, specifically comparing Example 1 with Example 17, the types of doping elements of the nickel-cobalt-manganese-aluminum quaternary positive electrode material and the lithium iron phosphate positive electrode material in Example 17 are inconsistent, resulting in a decrease in lithium ion transmission and electron transmission performance, which reduces the electrochemical performance of the compounded positive electrode material, that is, the performance of the battery is reduced. Fourthly, specifically comparing Example 1 and Example 18, the doping elements of the nickel-cobalt-manganese-aluminum quaternary positive electrode material and the lithium iron phosphate positive electrode material in Example 18 are both Mg, and the performance improvement effect of Mg on these two materials is relatively poor. This may be because when Mg participates in the synthesis of these two materials, the crystal structure jointly formed has relatively poor stability, and is not conducive to the deintercalation and extraction of lithium ions, thereby reducing the lithium ion transmission efficiency, and ultimately causing a decline in the battery performance in various aspects.

[0273] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A positive electrode material, characterized in that: Including nickel-cobalt-manganese-aluminum quaternary positive electrode materials and lithium iron phosphate positive electrode materials; The chemical formula of the nickel-cobalt-manganese-aluminum quaternary positive electrode material is Li (1+u) Ni v Mn w Co x Al y A z O2, where u≥0, v+w+x+y+z=1; The chemical formula of the lithium iron phosphate positive electrode material is Li 1+k Fe(PO4) 1+m B n , where k, m, n ≥ 0; Among them, A and B are both doping elements; The mass ratio of the nickel-cobalt-manganese-aluminum quaternary positive electrode material and the lithium iron phosphate positive electrode material is (0.5-7.0): (3.0-9.5).

2. The positive electrode material according to claim 1, characterized in that: The doping element A includes at least one of Ti, K, Ca, Sc, V, Rb, Sr, Y, Zr, Nb, Mo, Te, and Ru.

3. The positive electrode material according to claim 1, characterized in that: The doping element B includes at least one of Ti, K, Ca, Sc, V, Rb, Sr, Y, Zr, Nb, Mo, Te, and Ru.

4. The positive electrode material according to claim 1, characterized in that The particle size of the positive electrode material is 0.1-2 μm, and the particle size distribution is: the mass proportion of 0.1-0.3 μm is 35-45%, the mass proportion of 0.3-0.5 μm is 15-25%, the mass proportion of 0.5-1 μm is 15-25%, the mass proportion of 1-1.5 μm is 5-15%, and the mass proportion of 1.5-2 μm is 5-15%.

5. The positive electrode material according to claim 4, characterized in that The particle size distribution of the positive electrode material is as follows: 0.1-0.3 μm accounts for 40% by mass, 0.3-0.5 μm accounts for 20% by mass, 0.5-1 μm accounts for 20% by mass, 1-1.5 μm accounts for 10% by mass, and 1.5-2 μm accounts for 10% by mass.

6. The positive electrode material according to claim 1, characterized in that: In the nickel-cobalt-manganese-aluminum quaternary positive electrode material, the doping amount of the doping element A is 200 to 6000 ppm.

7. The positive electrode material according to claim 1, characterized in that: In the lithium iron phosphate positive electrode material, the doping amount of the doping element B is 200 to 6000 ppm.

8. A method for preparing the positive electrode material according to any one of claims 1 to 7, characterized in that: The steps include: S1. Mixing the nickel-cobalt-manganese-aluminum quaternary positive electrode material and the lithium iron phosphate positive electrode material in water, and grinding the particles in the mixed system to a particle size of 1 to 10 μm to obtain a slurry; S2. The slurry is spray dried at a drying temperature of 90 to 100°C, and the particle size after drying is controlled to be 5 to 20 μm; S3. Then, jet milling and mechanical milling are performed in sequence to obtain the positive electrode material.

9. A positive electrode sheet, characterized in that: The positive electrode material comprises the positive electrode material as claimed in any one of claims 1 to 8; and the compaction density of the positive electrode sheet is 3.2 to 4.2 g / cm 3 .

10. A battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Anode active material composition of lithium ion secondary battery and battery

    CN101295780A

  • Method for preparing lithium iron phosphate and lithium nickel cobalt manganese oxide composite cathode material

    CN104377353A

  • Quaternary positive electrode material and preparation method thereof

    CN113036117A

  • Lithium iron phosphate positive electrode material and preparation method and application thereof

    CN118324110A

  • Nonaqueous electrolyte secondary cell

    CN1350342A

Cited By

  • Positive electrode material, preparation method therefor, positive electrode sheet, and battery

    EP4779695A1

  • Positive electrode material, preparation method therefor, positive electrode sheet, and battery

    WO2026086032A1